2017
DOI: 10.4038/jbs.v4i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive model for understanding and enhancing pro-environmental purchase behavior: Towards a conceptual framework

Abstract: Inculcating pro-environmental purchase behavior is beneficial to both individuals and the society at large. The TPB has been generally applied to understand and examine pro-environmental purchase behavior. However, as the underpinnings of this theory are not adequate to understand the entire process of the development of pro-environmental purchase behavior, a more comprehensive theoretical framework is required. Combining the TPB with the VBN Theory provides such a comprehensive theoretical framework. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…Individuals perceive environmental responsibility as a response to moral responsibility, which plays a key role in amplifying intrinsic motivation and reinforcing their willingness to act. Research has shown that by incorporating environmental responsibility into theoretical models of planned behavior, environmental behavioral intentions can be predicted more accurately (Hines et al, 1987 ; Achchuthan et al, 2017 ; Rezaei et al, 2019 ). Thus, we propose the following hypothesis:…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Individuals perceive environmental responsibility as a response to moral responsibility, which plays a key role in amplifying intrinsic motivation and reinforcing their willingness to act. Research has shown that by incorporating environmental responsibility into theoretical models of planned behavior, environmental behavioral intentions can be predicted more accurately (Hines et al, 1987 ; Achchuthan et al, 2017 ; Rezaei et al, 2019 ). Thus, we propose the following hypothesis:…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Revisión teórica Achchuthan et al (2017), Ajzen y Driver (1991), Ajzen (2002), Castañeda (2017), Chamorro y Bañegil (2006), Danciu (2018), Dunlap et al (2000), Higuchi (2015), Neagu (2012), Peattie (2010), Pires et al (2014), Rana y Paul (2017), Reynolds et al (2015), Sima (2014), Stern (2000) Estudios empíricos cuantitativo Regresión múltipleanálisis de varianza Aertsens et al (2011), da-Silva et al (2013, Kumar (2013), Melo et al (2019) Fuente: elaboración propia.…”
Section: Tipo De Estudio Tipo De Análisis Referenciasunclassified
“…Es común que consumidores con ingresos bajos sean muy susceptibles al precio(Feraz et al, 2017;Rana y Paul, 2017;Zhang et al, 2018). En algunas otras publicaciones(Achchuthan et al, 2017;Teng y Lu, 2016;Wang, 2017;Wang et al, 2017), se menciona la importancia del valor percibido de los clientes frente a la intención de compra de estos productos; debe tenerse en cuenta que esta variable es muy amplia, lo cual implica que son influenciados por la calidad, los riesgos, la publicidad y otros, que también pueden modificar la intención de compra. Por lo tanto, sería valioso tener un modelo integral que incorpore y valide diferentes variables y tenga en cuenta su prioridad para los clientes y cómo influyen en la intención de compra.En consecuencia, se hace necesario constituir futuras líneas de investigación que busquen comprender mejor cómo se lleva a cabo el proceso de decisión de compra de un producto orgánico por parte de los consumidores y, con este fin, recurrir a teorías del comportamiento basadas en la TPB para comprender mejor las diferentes variables que afectan este proceso.…”
unclassified